1999
DOI: 10.1097/00003246-199906000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triage decisions for intensive care admission

Abstract: Physicians triage patients to intensive care based on the number of beds available, the admission diagnosis, severity of disease, age, and operative status. Admitting patients to intensive care is associated with a lower mortality rate, especially in patients with APACHE scores of 11 to 20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
161
12
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(207 citation statements)
references
References 24 publications
21
161
12
13
Order By: Relevance
“…Mortality outside the ICU was regrettably much higher, up to 53% (28). This has been confirmed by other reports (29)(30)(31)(32)(33)(34)(35), and it strongly suggests that all patients with severe sepsis and septic shock should be admitted to the ICU.…”
Section: Discussionsupporting
confidence: 68%
“…Mortality outside the ICU was regrettably much higher, up to 53% (28). This has been confirmed by other reports (29)(30)(31)(32)(33)(34)(35), and it strongly suggests that all patients with severe sepsis and septic shock should be admitted to the ICU.…”
Section: Discussionsupporting
confidence: 68%
“…First, it was performed in a single country. Previous studies have shown that haematological patients are often denied ICU admission based on guidelines from learned societies [30][31][32]. However, guidelines are applied in a uniform manner across industrialised countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…The three case volume tertiles were: low volume (,12 admissions per year), intermediate volume (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) admissions per year), and high volume (.30 admissions per year). In univariate analyses, ICU case volume was not associated with ICU mortality.…”
mentioning
confidence: 99%
“…However, in the past decade, there have been several reports of patients appropriately referred to, but refused, ICU admission [2,3,[8][9][10][11][12]. These studies can be used to compute the mortality risk reduction achieved by intensive care.…”
mentioning
confidence: 99%